DISASTER PREPAREDNESS BASED TOURISM IN ANYER, SERANG REGENCY - Marningot Tua Natalis Situmorang (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The marine and coastal area in Anyer is a marine tourism area that has become a major tourist destination or destination in recent years. After the Mount Anak Krakatau tsunami in December 2018, the number of tourists who came to Anyer and its surroundings decreased considerably. The main cause of the decline in the number of tourists is the lack of safety guarantees if they visit this area, this is due to the lack of information about the early warning system, the lack of knowledge of tourists in disaster management and the absence of infrastructure that becomes a place of protection when a disaster occurs, such as: evacuation routes, shelters etc. The objectives and targets of this Community Service activity are: (1) providing knowledge and understanding and creating a tourist culture that is alert and adaptive to the threat of disaster; (2) reduce vulnerability and increase the capacity of tourists both individually, households and communities in dealing with and dealing with disasters; (3) prepare a draft action plan for disaster risk reduction in the tourism area of ​​Anyer, Serang Regency. This activity uses the personal disaster-based tourism method which is carried out directly at the tourist site. In its implementation, this method begins by introducing tourist locations from the entrance to the exit, and several alternative evacuation routes, and several incidents that have occurred and may occur, lectures - discussions (questions and answers) - then practice directly on the spot. The advantage of this method is that participants can immediately practice what they hear and see, while the disadvantage is that it tends to depend on the extension agent and maybe carrying out the practice is only an obligation as a visitor. The location for the implementation of this service is the tourist area of ​​Anyer, Serang Regency. This Community Service Activity was carried out for tourist visitors in Anyer, Serang Regency in April 2020. From the activities carried out it can be concluded that the capacity of tourists' understanding of disaster preparedness is still lacking, the infrastructure for evacuation has not been effective in the absence of adequate evacuation routes, absence disaster shelter or post, and there is no disaster evacuation indicator / sign.